Characterization of KRAS Mutational Regression in Oligometastatic Patients - Ottaiano, Alessandro; de Vera d’Aragona, Roberta Penta; Trotta, Anna Maria; Santorsola, Mariachiara; Napolitano, Maria; Scognamiglio, Giosuè; Tatangelo, Fabiana; Grieco, Paolo; Zappavigna, Silvia; Granata, Vincenza; Perri, Francesco; Luce, Amalia; et al. (Frontiers in Immunology, 2022)
Background We previously reported rare regressive genetic trajectories of KRAS pathogenic mutations as a specific hallmark of the genuine oligometastatic status in colorectal cancer (CRC). Methods Survival and prognostic impact of disease extent in 140 metastatic CRC patients were evaluated through the Kaplan–Meyer curves and the Log-Rank test. KRAS mutations were assessed through the Illumina NovaSeq 6000 platform and TruSight™ Oncology 500 kit. HLA typing was carried out by PCR with sequence-specific oligonucleotides. Lymphocyte densities in tumors were expressed as cells per square millimeter. NKs isolated and CD8+ from NK-depleted PBMCs were characterized through flow cytometry. CD107a externalization was evaluated as NKs/CD8 cytotoxicity toward human colon cancer cells HT29, SW620, HCT116, and LS174T carrying different KRAS mutations. Results The oligometastatic status was a strong and independent variable for survival (HR: 0.08 vs. polymetastatic disease; 95% CI: 0.02–0.26; p < 0.001). Eighteen oligometastatic patients were selected. Twelve were alive at the last follow-up, and 9 were characterized. Genetic regression of KRAS was observed in 3 patients: patient (PAT)2, PAT5, and PAT8. PAT2 and PAT5 presented the highest levels of GrzB+ lymphocytes in the tumor cores of the metastases (120 ± 11.2 and 132 ± 12.2 cells/mm2, respectively). Six out of 9 patients (67%), including PAT2 and PAT5, expressed HLA-C7. Twopatients (PAT2 and PAT5) presented high CD3+/CD8+-dependent cytotoxicity against HLA-C7+ SW620 cells (p.G12V-mutated cells), which was consistent with their observed mutational regression (p.G12V/p.G13D in primary→p.G13D in metastatic tumor). Conclusions We provide evidence that CD3+/CD8+ lymphocytes from oligometastatic CRC patients display differential cytotoxicity against human colon cancer cells carrying KRAS mutations. This could provide an interesting basis for monitoring oligometastatic disease and developing future adoptive immunotherapies.